Pembelajaran Bahasa Inggris dalam Kurikulum Merdeka di Tingkat Pendidikan Menengah Pertama: Kajian Literatur - Nabilah, Nur Ainiyatun (Maliki Interdisciplinary Journal, 2025)
The riview analyze English language learning within the Merdeka Curriculum at the lower secondary education level. This research highlights the role of technology, digital challenges, and strategies that can be employed to improve learning outcomes. Although the Merdeka Curriculum provides flexibility and opportunities to enhance skills in the modern era, it still faces several challenges, such as limited direct interaction between teachers and students, unequal access to technology, and language distortion caused by informal digital communication. The study finds that the use of lightweight applications, the provision of offline learning materials, and the optimization of school facilities can help overcome technological limitations. To improve language use in academic settings, it is also necessary to cultivate the habit of using formal language and implement digital language etiquette. Additionally, strengthening interaction through online consultation sessions, synchronous discussions, and collaborative projects is essential to maintaining the quality of communication and learning. Overall, the findings indicate that inclusive technological integration, appropriate pedagogical support, and balanced social interaction are key factors for the success of English language learning within the Merdeka Curriculum in the digital era.